2017
DOI: 10.5534/wjmh.2017.35.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics and Treatment Outcomes of Penile Cancer

Abstract: PurposeThe aim of this study was to assess the clinicopathologic characteristics of penile cancer, including patterns of therapy, oncologic results, and survival.Materials and MethodsBetween January 2005 and July 2015, 71 patients at 6 institutions who had undergone penectomy or penile biopsy were enrolled. Their medical records were reviewed to identify the mode of therapy, pathology reports, and cancer-specific survival (CSS) rate.ResultsClinicopathologic and outcome information was available for 52 male pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
3
6
1
1
Order By: Relevance
“…younger males. [10][11][12] In this study, we found it be more common in men above 60 years. Men who are unmarried, divorced or separated are more prone to the disease.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…younger males. [10][11][12] In this study, we found it be more common in men above 60 years. Men who are unmarried, divorced or separated are more prone to the disease.…”
Section: Discussionsupporting
confidence: 55%
“…13,14 The disease may occur at any site, however, the glans penis is the most common primary site and well to moderately differentiated squamous cell carcinoma is the most common histological grade. 11,15 Patients In the present study, we compared the SEER stage, AJCC stage, and TNM stage with or without TG to predict the CSM free survival after PTE. Our model showed Our results are comparable to the results of the study conducted by Thuret et al Analyzing their findings, TNM stage (78%) was more accurate than AJCC stage (77.2%) in predicting 5-year CSM free rates.…”
Section: Discussionmentioning
confidence: 99%
“…Aita et al claimed that high histopathological grade was responsible for a poor prognosis based on a study with an average follow-up more than 3 years involving 163 PC patients [30]. Other studies also emphasized the importance of pathologic grade [31,32]. But, in our study, it seemed that the histopathological grade played a different role in the assessment of patients' prognosis except for the grade III.…”
Section: Discussioncontrasting
confidence: 53%
“…This is the most frequent histological type, other histological forms are rare. Nam et al [15] reported 2 cases of leiomyosarcoma, a penile location of a large B-cell non-Hodgkin's lymphoma was described in the series of Sow et al [9]. Squamous cell carcinoma of the penis has a slow progression, first locally, then secondarily regionally by invasion of the inguinal lymph nodes, and finally the pelvic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%